Heat loss by the Earth, geothermal energy and geothermal heat pumps - Duque, Maria Rosa (2012)
Heat loss by the Earth, geothermal energy and geothermal heat pumps Maria Rosa A. Duque (1) (1)Departamento de Física da Universidade de Évora, Rua Romão Ramalho 59, 7000-671 Évora Phone Number 351 266745372; E-mail: mrad@uevora.pt Geothermal energy is often labeled as renewable and sustainable. It is listed together with solar, wind and biomass as alternative energy options in governmental R& D programs. The temperature in the Earth’s interior increases with depth. This fact is responsible for the heat flow, from the interior to the surface. Heat loss through the Earth was calculated using heat flow density values obtained in continents and oceans. The result obtained [1] for the total heat loss is 46± 2 TW. Heat loss through continents is 14 TW. The direct use of geothermal energy dates back thousands of years when people began using hot springs for bathing and cooking. Today, geothermal energy can be used to generate electricity or directly in many applications. Worldwide direct utilizations of geothermal energy in 2005 was [2] 273372TJ/year, of which 32% were obtained through geothermal heat pumps. At this time, the equivalent annual savings in fuel oil amounts to 170 million barrels and 24 million tons in carbon emissions to the atmosphere. Since 2005, the use of geothermal heat pumps has been wide in both residential and commercial buildings, due to the attractive advantages of high efficiency and environmental friendliness. Geothermal heat pumps are similar to ordinary heat pumps, but instead of using heat found in the outside air of the building, they use heat from the earth to provide heating, air conditioning and, in most cases, hot water. In winter, they move the heat from the earth to the buildings. In summer, they pull the heat from the buildings and discharge it into the ground. The ground source heat pumps comprise a wide variety of systems that may use ground water, ground, or surface water as heat sources or sinks. In this work, we will talk about the different systems that may be used, their efficiency and also about the problems that can be associated with them. As a conclusion, we can say that geothermal heat pumps can be a near future / present day means of using the heat from the ground to cool or warm the buildings, in cold or hot weather conditions. The energy saving potential is significant and air pollution will be reduced. References [ 1] C. Jaupart et al, “Treatise on Geophysiscs vol 2”,D.Bercovici and G.Schubert, 2007. [2] J.W. Lund, D.H.Freeston and T.L.Boyd,Geothermics,34,(2005) p.691.